A study of combined low salinity foam injection using dlvo theory and surface complexation modeling - Hassan, A.M. (Offshore Technology Conference, 2020)
The proposed study of combined low salinity foam Injection using DLVO-theory (i.e., Derjaguin, Landau, Verwey, and Overbeek) and surface complexation modeling or SCM, is a follow up of a previous study of a Novel Hybrid Enhanced Oil Recovery Method by Smart Water-Injection and Foam-Flooding in Carbonate Reservoirs (SPE-196407-MS). The method combines the advantages of our new designed "smart-water" (i.e., ionically modified brine or low salinity) injection with foam drive recovery. Our new desined "smart-water" injection has a double enhancement effect. It leads to change the limestone rock (i.e., calcite) wettability from oil or mixed-wet to more water wet (i.e., stable water-film), and helps to improve the stability of the foam-film. In the previous study (SPE-196407-MS) we investigated the impact of our "smart water" or low salinity injection on the surface complexes by simulating one single base case scenario, which equivalent to NaCl 0.4 mMol/liter. We use computr program (PHREEQC) to obtain the equilibrium concentrations and zeta-potential (surface potential or electro-kinetic potential), and to invetigate the effect of water-salinity and CO2 pressure for a given choice of the surfactant (i.e. carboxylic acid R-COOH). In addition, for the surface complexation model, we studied the model of Dzombak and Morel, which uses Debye Huckel activity coefficients (i.e., valid up to ionic strength I = 0.3 mol/kilogram of water) (SPE-196407-MS). In this contribution (OTC-30301-MS), we use the DLVO-theory and SCM (surface complexation modeling) to create multiple scenarios of smart water (i.e., ionically modified brine) to study its impact on surface complexes during fluid-rock interaction process (i.e., calcite-water interface and oil-water interface). To be specific, we use PHREEQC to simulate and compare two case scenarios; the case of low salinity (NaCl 0.4 mmol/kg-water) and the case of high salinity NaCl 8500 mMol/liter. Also, for better optimization of the factors affecting the surface complex modeling, in this work, we modified the model of Dzombak and Morel, by using more accurately activity coefficient given by Pitzer coefficients above (0.3 mol/kgwater) (i.e., valid up to ionic strength I = 6 mol/kg-water). Additionally, the surface charge and the surface complexes are calculated, implemented and built-in using geochemical code PHREEQC. Further input: fraction of sites that bind the carboxylic acids (R-COOH) and bind the carbonates (CaCO3) surface complex are (1.67Ã10â6) and (4.1 Ã 10-6) respectivly, and surface area per gram of solid is (1 m2/g) for both the oleic and calcite interface (Hassan, et al., 2020). Moreover, we applied Gibbs rule to determine the number of chemical degrees of freedom. In our case, we have two numbers of degrees of freedom, and its chosen to be pH and ionic strength. Also, we examined the effect of pH and carbon dioxide (CO2)-pressure on the surface complexes (i.e., surface charge and surface potential) for both scenarios (i.e., low salinity NaCl 0.4 mmol/kg-water and high salinity NaCl 8500 mmol/kg-water) (Hassan, et al., 2020). Qualitatively we can state that, the stability of a water film between the rock-aqueous phase / oil aqueous phase interfaces is resolute by the active sites on carbonate rock (i.e., calcite) and oil. If they with a charge of the same sign, a water film is usually stable. The foam stability is determined by the double layer (charged surface + counter ions in solution) repulsion, which is electrostatic and attractive the Van der Waals forces, which are determined by the dielectric coefficients of the constituting layers. If the electrostatic forces dominate the foam film is considered stable. It is conjectured that, high carbon dioxide pressures have a destabilizing effect on the film for both cases (i.e., low salinity NaCl 0.4 mmol/kg-water and high salinity NaCl 8500 mmol/kg-water), as they reduce the surface potential. A decreased surface potential leads to a reducing electrostatic double layer repulsion (EDL) and thus destabilizes the stability of the foam film, whereas low salinity leads to less screening of the surface potential and thus improves the stability of the foam film lamellae. The activity coefficients are more accurately given by the Pitzer coefficients above (0.3 mol/kg-water) (i.e., valid up to 6 mol/kg-water). It is shown that, manipulating surface complexes by imposing different salinity and pH can help to obtain mixed-wet or oil-wet behavior, with more favorable residual oil saturations, accepting the occurrence of less favorable mobility ratios. Clearly, the choice of optimal conditions is case dependent; if the mobility ratio is already favorable as to be expected with foam flow, mixed-wet conditions are favored with low residual oil saturations. Thus, an optimal choice of the pH that at the same time leads to a stable brine film on the calcite surface, and a stable foam film requires fine tuning. Copyright 2020, Offshore Technology Conference